The Scientific Heritage of R. G. Fakhrutdinov (According to materials of the fund No. 17 of the Museum of Archaeology of Tatarstan Republic of the Institute of Archaeology named after A. Kh. Khalikov) - Galina I. Drozdova (Археология евразийских степей, 2022)
The article describes the scientific fund of the famous Kazan archaeologist, student of A.Kh. Khalikov, Honored scientist of the Republic of Tatarstan – Ravil Gabdrakhmanovich Fakhrutdinov. The fund consists of 10 inventories. Inventory 1 includes research materials, the 2nd inventory reveals the scientific and organizational side of the researcher's activities, who has worked all the years in the Institute of Language, Literature and History of Kazan Branch of the USSR Academy of Sciences, since 1997 in Institute of History of the Academy of Sciences of the Republic of Tatarstan. Inventory 3 includes biographical materials, inventory 4 consists of the correspondence of R.G. Fahrutdinov. The 5th inventory contains prints of articles presented to him by the authors of the works. Inventory 6 contains materials of other persons. Inventory 7 is presented with materials on various topics that the scientist was engaged in. Inventory 8 includes extracts from literature and other sources for writing scientific papers. The 9th inventory contains different materials. Inventory 10 consists of publications about R.G. Fakhrutdinov.